2021
DOI: 10.3389/fmicb.2021.598498
|View full text |Cite
|
Sign up to set email alerts
|

Cephalosporins Interfere With Quorum Sensing and Improve the Ability of Caenorhabditis elegans to Survive Pseudomonas aeruginosa Infection

Abstract: Pseudomonas aeruginosa utilizes the quorum sensing (QS) system to strategically coordinate virulence and biofilm formation. Targeting QS pathways may be a potential anti-infective approach to treat P. aeruginosa infections. In the present study, we define cephalosporins’ anti-QS activity using Chromobacterium violaceum CV026 for screening and QS-regulated mutants of P. aeruginosa for validation. We quantified the effects of three cephalosporins, cefepime, ceftazidime, and ceftriaxone, on (1) pyocyanin producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…The efficacy of purified compounds on inhibiting QS mechanisms was screened using indicator organisms Chromobacterium violaceum CV026 and Agrobacterium tumefaciens A136. Overnight grown C. violaceum CV026 culture (1 ml) (OD 600 ≈ 0.1) was added into 100 ml LB agar medium supplemented with kanamycin (20 μg/ml) and C6-HSL (5 μM), mixed, and poured into the plates ( Kumar et al, 2021 ). After the medium was solidified, 2 μl of samples ( 1–4 ) (50 mg/ml) were dropped onto the plates and then incubated at 28°C for 24 h, recording the violacein changes in color.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of purified compounds on inhibiting QS mechanisms was screened using indicator organisms Chromobacterium violaceum CV026 and Agrobacterium tumefaciens A136. Overnight grown C. violaceum CV026 culture (1 ml) (OD 600 ≈ 0.1) was added into 100 ml LB agar medium supplemented with kanamycin (20 μg/ml) and C6-HSL (5 μM), mixed, and poured into the plates ( Kumar et al, 2021 ). After the medium was solidified, 2 μl of samples ( 1–4 ) (50 mg/ml) were dropped onto the plates and then incubated at 28°C for 24 h, recording the violacein changes in color.…”
Section: Methodsmentioning
confidence: 99%
“…The functionality of quorum-sensing systems resides on basic components that are druggable and tend to be absent in mammals ( LaSarre and Federle, 2013 ; Fleitas Martínez et al, 2019b ; Ellermann and Sperandio, 2020 ). Similarly to the observed in bacterial secretion systems, mutant strains in quorum sensing system components could become avirulent strains in infection models ( Askoura et al, 2021 ; Kumar et al, 2021 ). Studies focused on quenching quorum sensing systems with inhibitors have demonstrated that targeting these communication systems is a promising strategy to face resistant pathogens ( Sully et al, 2014 ; Daly et al, 2015 ; Parlet et al, 2019 ; Salam et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%
“…Computational analysis provides an excellent tool to simulate the ligand-receptor interactions at the atomic level ( Kumar et al., 2021 ). Hence, in silico analysis was carried out to gain better insights into the possible associations between CiNN and the QS receptors of P. aeruginosa .…”
Section: Discussionmentioning
confidence: 99%
“…Since QS functions as an auxiliary factor that promotes pseudomonal virulence, its abrogation using QS inhibitors may possibly minimize the risk of exerting any selection pressure for the emergence of anthropogenic resistance, a phenomenon commonly witnessed with conventional antibiotic therapy ( Rasmussen and Givskov, 2006 ). The fascinating property of a potent quorum quenching (QQ) agent is that it attenuates QS circuits of a pathogen at sub-inhibitory concentrations (sub-MICs) by either degrading the QS molecule or by abrogating its interaction with their cognate receptors without directly targeting the vital pathways required for bacterial survival ( Kumar et al., 2021 ). Since this strategy does not impose any survival threat, the probability of developing resistance against the anti-QS drugs also remains low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation